Nutritional Epidemiology Study: Prevalence of Vitamin and Mineral Supplement Use and Correlated Factors among University Students in Jordan - Ibrahim, Mohammed O. (Pakistan Journal of Nutrition, 2018)
Objective: This study was carried out to determine the prevalence and associated factors of vitamin-mineral supplements use among University students. Methods: A cross-sectional study applied a quantitative research approach using a self- administrated questionnaire given to University students in Jordan. Results: The prevalence of vitamin-mineral supplement use was 23%. The main reasons for using vitamin mineral supplements were ‘to maintain good health’ (73%), followed by ‘to lose weight’ (11%). Vitamin-mineral supplement use among participants was significantly (p